The city and emptiness - Salmin, Leonid (project baikal, 2021)
The article presents the author’s phenomenological study of emptiness with regard to the urban space. Studying the cases of three historical cities, the author analyses the meanings of emptiness coming out against the background of fatal external threats. The notion of emptiness is introduced into the symbolic and semiologic discourse of the city.
Keywords: city; emptiness; meaning; space; spatial form; corporeality; visual image